2011
DOI: 10.3329/jhpn.v29i5.8895
|View full text |Cite
|
Sign up to set email alerts
|

Five Pond-centred Outbreaks of Cholera in Villages of West Bengal, India: Evidence for Focused Interventions

Abstract: In rural West Bengal, outbreaks of cholera are often centred around ponds that is a feature of the environment. Five investigations of laboratory-confirmed, pond-centred outbreaks of cholera were reviewed. Case-control odds ratios were approximated with relative risks (RRs) as the incidence was low. The environment was investigated to understand how the pond(s) could have become contaminated and could have infected villagers. The five outbreaks of cholera in 2004-2008 led to 277 cases and three deaths (median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…In India, most cholera outbreaks have been caused by the consumption of contaminated drinking water (39,43,44,46). In some studies in India, cholera outbreaks were found to be associated with the handling of contaminated water from a pondconnected tube well (15,22,50). One water-borne cholera outbreak occurred after the impact of Cyclone Aila in West Bengal, India, in May 2009 owing to the resulting disruption of the water distribution system in the affected areas (37,38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, most cholera outbreaks have been caused by the consumption of contaminated drinking water (39,43,44,46). In some studies in India, cholera outbreaks were found to be associated with the handling of contaminated water from a pondconnected tube well (15,22,50). One water-borne cholera outbreak occurred after the impact of Cyclone Aila in West Bengal, India, in May 2009 owing to the resulting disruption of the water distribution system in the affected areas (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…Contaminated imported seafood products were identified as a major source for a cholera outbreak in Singapore in October 2004 (23). An additional 44 people suffered from two consecutive cholera outbreaks in Tak (16) 2003 Miri, Indonesia Contaminated water (17) 2003 Karachi, Pakistan Contaminated water (18) 2004 Mathbaria, Bangladesh Contaminated water (18) 2004 Mathbaria, Bangladesh Contaminated water (18) 2004 Bakherjanj, Bangladesh Contaminated water (19) 2004 Bhind, India Contaminated water (20) 2004 Kolkata, India Contaminated water from leaked pipelines (21) 2004 Kashmir, India Contaminated water (22) 2004 South 24 Parganas, West Bengal, India Contaminated pond water (21) 2004 Myanmar Heavy rainfall leading to contamination of water (21) 2004 Singapore Contaminated food (23) 2004 Bedok and Tampines, Singapore Contaminated imported seafood Screening of food handlers (18) 2005 Mathbaria, Bangladesh Contaminated water (18) 2005 Bakherjanj, Bangladesh Contaminated water (24) 2005 Delhi, India Contaminated water (25) 2005 Sangli, Maharastra, India Contaminated water (26) 2005 Orissa, India Contaminated food products and water (27) 2006 Kolkata, India Contaminated water Discarding unsafe water and chlorination (28) 2006 Orissa, India Contaminated water (22) 2006 South 24 Parganas, West Bengal, India Contaminated pond water (29) 2006 Andaman and Nicobar Island, India Contaminated pond water Chlorination of water (30) 2006 Garulia, West Bengal, India Contamination of water and low chlorine content Repair of leakage and chlorination of water (22) 2007 South 24 Parganas, West Bengal, India Contaminated pond water (31) 2007 Orissa, India Contaminated water (32) 2007 Orissa, India Contaminated water (33,34) 2007 Thateng and Lamam, Laos, PDR Contaminated water, interpersonal transmission Providing safe water, improving water, sanitation, and health education (35) 2007 Xekong province, Laos Contaminated water (36)<...>…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study done in West Bengal, they have also found that washing utensils, bathing, drinking, washing faces were the significant risk factors for the outbreak of cholera. 9 Cholera outbreak exhibits seasonal pattern and that pattern differs by latitude. In Pakistan, several studies have reported, classical strain is most incident from November to January and from April to May while in Kolkata, India, seasonal pattern of cholera cases peak in April, May, and June.…”
Section: Discussionmentioning
confidence: 99%
“…From 2008 to 2015, one million deaths have been recorded in Pakistan alone which reflects the severity and primarily significance of this notorious infection [2]. Outbreaks of gastroenteritis primarily depends upon a variety of risk factors among children and adults such as contaminated pond water which was used for washing, bathing, drinking and cooking purposes without boiling [3], use of smokeless tobacco [4], malnutrition, excessive use of antibiotics as well as psychological factors such as anxiety, depression [5] and immunocompromised patients [6].…”
Section: Introductionmentioning
confidence: 99%